Fullerene C-60 Coated Silicon Nanowires as Anode Materials for Lithium Secondary Batteries - Arie, Arenst Andreas; Lee, Joong Kee (AMER SCIENTIFIC PUBLISHERS, 2012)
A Fullerene C-60 film was introduced as a coating layer for silicon nanowires (Si NWs) by a plasma assisted thermal evaporation technique. The morphology and structural characteristics of the materials were studied by scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS). SEM observations showed that the shape of the nanowire structure was maintained after the C-60 coating and the XPS analysis confirmed the presence of the carbon coating layer. The electrochemical characteristics of C-60 coated Si NWs as anode materials were examined by charge-discharge tests and electrochemical impedance measurements. With the C-60 film coating, Si NW electrodes exhibited a higher initial coulombic efficiency of 77% and a higher specific capacity of 2020 mA h g(-1) after the 30th cycle at a current density of 100 mu A cm(-2) with cut-off voltage between 0-1.5 V. These improved electrochemical characteristics are attributed to the presence of the C-60 coating layer which suppresses side reaction with the electrolyte and maintains the structural integrity of the Si NW electrodes during cycle tests.
Keywords: ION BATTERIES